SURVEILANS EPIDEMIOLOGY FAKTOR RISIKO COVID-19 DI DESA ADAT TANGSUB DAN CEMANGGON CELUK SUKAWATI GIANYAR - dewa ayu agus, sri laksemi (Buletin Udayana Mengabdi, 2020)
Community service activities are carried out through the Community Empowerment Learning Real Work Lecture program conducted at the Tangsub and Cemanggon banjar, Celuk Village, Sukawati District, Gianyar Regency aimed at the risk of COVID-19 transmission to the residents of Tangsub and Cemanggon Celuk Traditional Villages. The activity begins by asking for approval with the village head, preparing a questionnaire in the form of a google form related to risk factors for Covid-19 transmission and distributing it through the Whatsapp group. Apart from using the google form, print out questionnaires were also distributed by visiting residents' homes accompanied by local community leaders following the COVID-19 prevention protocol. After the risk factor data has been collected, a descriptive analysis is carried out in the form of graphs and tables. Health surveillance activities, screening for COVID-19 risk factors were obtained by 146 respondents from Banjar Tangsub and Banjar Cemenggaon residents who filled out questionnaires. After doing the percentage of residents' risk status for Covid-19, it was found that 97% of citizens with low risk status, 3% of citizens with moderate risk status and 0% of citizens with severe risk. Citizens with moderate status are citizens who are over 60 years of age and / or have chronic disease. This data can be used for Village and District leaders to create COVID-19 prevention and control programs in the Tangsub and Cemanggon Celuk Traditional Village Areas.